Optimising the allocation of fleet across business units - Le Riche, N. (Nicole) (University of Pretoria. Faculty of Engineering, Built Environment and Information Technology. Dept. of Industrial and Systems Engineering, 2019)
Mini Dissertation (B Eng. (Industrial and Systems Engineering))--University of Pretoria, 2018.